2018
DOI: 10.1007/s12288-018-1001-6
|View full text |Cite
|
Sign up to set email alerts
|

Anemia Among School Children in Ernakulam District, Kerala, India

Abstract: Anaemia has significant negative impact on the health of school children including poor scholastic performance and cognitive impairment. The present study was done with the objective to estimate the prevalence of anemia among school going children in Ernakulam district, Kerala and to determine a few factors associated with anemia. Hemoglobin of 880 students of 6th to 9th standard in 11 randomly selected schools of Ernakulam district was estimated using HemoCue 201 photometer. Prevalence of anaemia was expresse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 11 publications
2
10
0
1
Order By: Relevance
“…Schoolchildren aged 11–15 years were at two times higher risk of being anemic compared to younger age group. This finding is consistent with previous studies conducted among children in different countries [ 41 46 ], which could be explained by the hyperactivity during this age together with high demand of micronutrient and limited consumption of a variety of food sources due to the household food insecurity [ 47 ], which can be reduced by school feeding [ 48 , 49 ]. The gender female was also an independent risk factor of anemia, which is in line with previous studies [ 50 , 51 ].…”
Section: Discussionsupporting
confidence: 92%
“…Schoolchildren aged 11–15 years were at two times higher risk of being anemic compared to younger age group. This finding is consistent with previous studies conducted among children in different countries [ 41 46 ], which could be explained by the hyperactivity during this age together with high demand of micronutrient and limited consumption of a variety of food sources due to the household food insecurity [ 47 ], which can be reduced by school feeding [ 48 , 49 ]. The gender female was also an independent risk factor of anemia, which is in line with previous studies [ 50 , 51 ].…”
Section: Discussionsupporting
confidence: 92%
“…Similar results have been described by Rakesh et al in Kollam Kerala where 77.5% of female adolescents were anemic compared to 67% in males. 16 This difference was also seen in logistic regression analysis where female had an odds ratio of 1.740 (C.I -1.417-2.136) of being anemic. In a study in south west Ethiopia among school going adolescent girls the odds of anemia was 3.04 (1.41-6.57) among females compared to males.…”
Section: Discussionmentioning
confidence: 72%
“…18 But in a study conducted in Kollam, Kerala by Rakesh et al among 5-17 year old boys and girls the prevalence of anaemia was 72.3%. 16 Similarly Anagha et al in Kozhikode among 11-16 girls it was 75.57%. 23 But a study in Kottayam by Siva et al reported a very low prevalence of 21% among adolescent girls.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Almost similar prevalence rates have been reported among children from different districts of Punjab such as Amritsar (Majha), Ludhiana, Moga, Faridkot and Patiala (Malwa) (Sidhu et al, 2007;Gupta et al, 2011;Bhatia, 2013;Kaur et al, 2015;Garg and Bhalla, 2016). Contrarily, several studies reported much lower prevalence of anemia among school children from other states of India and worldwide (NFHS-4, 2015-16;Birhanu et al, 2018;Cruz-Gongora et al, 2018;Rakesh et al, 2018;Tezera et al, 2018). Similarly, regional disparities in the prevalence of anemia were observed in China, Brazil, Ghana and in 107 countries worldwide (Luo et al, 2011;Horta et al, 2013;Stevens et al, 2013;USAID, 2014).…”
Section: Prevalence Of Anemiamentioning
confidence: 54%